Activation and In Vivo Evolution of the MAIT Cell Transcriptome in Mice and Humans Reveals Tissue Repair Functionality - Hinks, Timothy S.C.; Marchi, Emanuele; Jabeen, Maisha; Olshansky, Moshe; Kurioka, Ayako; Pediongco, Troi J.; Meehan, Bronwyn S.; Kostenko, Lyudmila; Turner, Stephen J.; Corbett, Alexandra J.; Chen, Zhenjun; Klenerman, Paul; et al. (Cell reports (Cambridge), 2019)
Mucosal-associated invariant T (MAIT) cells are MR1-restricted innate-like T cells conserved across mammalian species, including mice and humans. By sequencing RNA from sorted MR1-5-OP-RU tetramer+ cells derived from either human blood or murine lungs, we define the basic transcriptome of an activated MAIT cell in both species and demonstrate how this profile changes during the resolution of infection and during reinfection. We observe strong similarities between MAIT cells in humans and mice. In both species, activation leads to strong expression of pro-inflammatory cytokines and chemokines as well as a strong tissue repair signature, recently described in murine commensal-specific H2-M3-restricted T cells. Transcriptomes of MAIT cells and H2-M3-specific CD8+ T cells displayed the most similarities to invariant natural killer T (iNKT) cells when activated, but to γδ T cells after the resolution of infection. These data define the requirements for and consequences of MAIT cell activation, revealing a tissue repair phenotype expressed upon MAIT cell activation in both species. [Display omitted] •We define the basic transcriptome of an activated MAIT cell in mice and humans•During acute infection, the MAIT cell transcriptome is most similar to iNKT cells•After the resolution of infection, MAIT cells more closely resemble γδ T cells•Both human- and murine-activated MAIT cells express a strong tissue repair signature Mucosal-associated invariant T (MAIT) cells are implicated in antibacterial and antiviral immunity. Using RNA sequencing of human MAIT cells stimulated with their cognate ligand and murine MAIT cells stimulated by acute Legionella infection, Hinks et al. report that activation leads to expression of a strong tissue repair signature in both species.